Design, in silico optimization, and generation of recombinant rabies virus glycoprotein: Paving the Way for Enhanced Vaccines: Design, In Silico Optimization, and Generation of Recombinant Rabies Virus Glycoprotein - Pazira, Saman; Hosseini, Seyed Masoud; Eghbali, Omid; Bashar, Rouzbeh; Pourhossein, Behzad; Fazeli, Maryam (Iranian Journal of Pharmaceutical Sciences, 2024)
Rabies is a fatal disease that may be transmitted from animals to humans. It is caused by a virus called rabies virus (RABV), which is a kind of RNA virus belonging to the family Rhabdoviridae and the genus Lyssavirus. Current rabies vaccines, while effective, require multiple doses for adequate protection, which presents significant financial and logistical challenges, especially in low-resource settings. Additionally, the risk of reversion to virulence in live-attenuated vaccines limits their use. This study aims to design and optimize the rabies virus glycoprotein (G protein) using in silico methods to address these challenges and develop a more effective and accessible rabies vaccine. The nucleotide sequences of the rabies virus glycoprotein were acquired from GenBank (accession number LT839616) and optimized to improve expression in Chinese Hamster Ovary (CHO) cells using bioinformatics tools. PSIPRED was employed for secondary structure prediction, and SWISS-MODEL was used for 3D structure modeling. The optimized gene was synthesized and inserted into the pcDNA3 vector. CHO cells were transfected with the recombinant plasmid, and the presence of the expressed gene was confirmed using RT-PCR and Western blot analysis. Optimizing the codons significantly enhanced the synthesis of the G protein derived from the rabies virus in CHO cells. Structural analyses confirmed the stability and proper conformation of the protein. The gene was successfully subcloned into the pcDNA3 vector, and its expression in CHO cells was verified using RT-PCR and Western blot analysis, demonstrating the effective production of the recombinant glycoprotein. This study successfully utilized bioinformatics and experimental methodologies to optimize the rabies virus G protein, demonstrating its potential as a viable vaccine candidate. The results provide a strong foundation for developing an advanced rabies vaccine that is both effective and accessible, particularly in regions where rabies remains prevalent.